Climate Change and Water Resources - Villalobos, Roberto (2008)
Water is a very essential one for the life and it is being affected by the climate change. The Climate Change Team of the National Meteorological Institute, knowing the importance of this, it has been given to the task of carrying out scientific studies that can offer to the country a guide of the efforts required to adapt to the effects of the climate change. The project Capacity Building for Stage II Adaptation to the Climate Change in Central America, Mexico and Cuba, allowed to the country to have an adaptation strategy of the water resources for the noroccidental region of the Great Metropolitan Area. It highlights the study of the current and future climatic risk in this regi